COMMUNICATION PATTERNS OF SINGLE MOTHERS IN THE EDUCATION OF ADOLESCENT CHILDREN IN MOJOKERTO - Putri, Salsabila Karina; S.Sos., M.I.Kom., Mutiah (The Commercium, 2024)
In 2022, there will be 4,253 couples in Mojokerto who will divorce, the causes are quarrels, economic problems, polygamy and apostasy. Jetis District in Mojokerto has the highest divorce rate, which has an impact on the increasing number of single parents. Divorce not only has an impact on husband and wife, but also on children, especially teenagers. The impact includes feelings of insecurity, loneliness, and feelings of guilt in children. Researchers used a qualitative approach with phenomenological methods and three communication patterns, namely, Authoritarian, Authoritative, and Permissive. The research results showed that of the 6 single parents studied, the family communication patterns applied varied, including Authoritarian, Authoritative, and Permissive. This research aims to understand how single parent mothers’ communication patterns influence their relationships with their teenage children and the formation of teenagers’ self-concept. In facing the challenging teenage years, effective communication between single parents and children is very important to ensure healthy development and a good relationship between the two. The research results showed that of the 6 single parents in Jetis, Mojokerto, there were variations in the family communication patterns they adopted. Most use authoritative patterns which have been proven to be effective in educating teenagers. proven authoritative, suitable for use by single parents educating teenage children.